Behavioral and electroencephalographic analysis of seizures induced by intrahippocampal injection of granulitoxin, a neurotoxic peptide from the sea anemone Bunodosoma granulifera - Santana, A.N.C. (2001)
In this study, the behavioral and electroencephalographic (EEG) analysis of seizures induced by the intrahippocampal injection in rats of granulitoxin, a neurotoxic peptide from the sea anemone Bunodosoma granulifera, was determined. The first alterations occurred during microinjection of granulitoxin (8 µg) into the dorsal hippocampus and consisted of seizure activity that began in the hippocampus and spread rapidly to the occipital cortex. This activity lasted 20-30 s, and during this period the rats presented immobility. During the first 40-50 min after its administration, three to four other similar short EEG seizure periods occurred and the rats presented the following behavioral alterations: akinesia, facial automatisms, head tremor, salivation, rearing, jumping, barrel-rolling, wet dog shakes and forelimb clonic movements. Within 40-50 min, the status epilepticus was established and lasted 8-12 h. These results are similar to those observed in the acute phase of the pilocarpine model of temporal lobe epilepsy and suggest that granulitoxin may be a useful tool not only to study the sodium channels, but also to develop a new experimental model of status epilepticus.